Henoch-Schönlein purpura with acute pancreatitis: analysis of 13 cases - Qin Zhang; Qi Guo; Ming Gui; Zhenhua Ren; Bo Hu; Ling Lu; Fang Deng (BMC, 2018)
Abstract Background Henoch-Schönlein purpura is a common small vessel vasculitis in children. Acute pancreatitis rarely presents as a complication of Henoch-Schönlein purpura and has not been well characterized. Methods We retrospectively reviewed 13 cases of Henoch-Schönlein purpura with acute pancreatitis among 3212 patients who attended our hospital between January 2003 and June 2016 and analyzed their clinical characteristics, laboratory findings, imaging findings, treatment and overall prognosis. Results All patients had abdominal manifestations, including significant abdominal pain (13/13), vomiting (9/13), abdominal distension (3/13) and melena (6/13). Serum amylase level significantly increased in all patients, and urine amylase was increased in 7 cases (7/10). However, increased urine lapse was only noted in 2 cases (2/5), and diffuse swelling of the pancreas was seen in 2 cases (2/13) by abdominal ultrasonography. Although all patients had typical skin purpura (13/13), 5 patients (5/13) with acute pancreatitis initially experienced acute abdominal pain in clinical onset of Henoch-Schönlein purpura. Glucocorticoid therapy was effective in alleviating abdominal symptoms of Henoch-Schönlein purpura patients with acute pancreatitis. All patients were in good general condition without any abdominal complications 6-12 months after discharge. Conclusions Acute pancreatitis is rarely observed in Henoch-Schönlein purpura children and has no specific clinical features that differentiate it from abdominal manifestations of Henoch-Schönlein purpura. Therefore, in Henoch-Schönlein purpura patients with severe abdominal pain, serum amylase levels should be assessed to confirm the diagnosis of acute pancreatitis. Early diagnose of Henoch-Schönlein purpura with acute pancreatitis and treatment timely was very important for good clinical outcomes.